Effect of elevate temperature on properties of self- compacting concrete containing steel fibers, glass fibre and polypropylene fibers - Venkadachalam, Gokulnath; Gupta, Vivek (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, an endeavour has been made to consider the utilization of glass fibre, steel fibre, and polypropylene fibre on the properties of self-compacting concrete (SCC), for example, compressive quality mass misfortune when presented to raised temperatures. The impact of glass fiber, steel fiber, and polypropylene fibre as fractional substitutions of concrete, added fibre (steel fibre, glass fibre, and polypropylene) content 1.2% for a mixture of concrete material, and utilizing M sand on the properties of SCC are researched. In a solid blend, three kinds of M20, M25, and M30 evaluations of cement were utilized. The examples of each solid blend were warmed up to various temperatures (room temperature, 100°C, 200°C). In every example of testing utilized on three kinds of temperature, the temperature was held steady at the greatest incentive for 0 hours, 60 minutes, or 2 hours before cooling. Utilizing Ordinary Portland concrete, an expansion of around 20–23% in compressive quality. was seen at 28 days when polypropylene content was diminished from 20% to 30% Also, test results obviously show that there is little improvement in compressive quality inside the temperature range of 100°C–200°C. Testing of Steel fibre on temperature 100°C, 200°C, has expanded compressive quality contrasted with the ordinary steel fibre concrete.